Wind-tunnel model of Shoreham Nuclear Power Station, Unit I, Long Island Lighting Company: progress report - Meroney, Robert N., author; Cermak, Jack E., author; Chaudhry, Fazal Hussain, author; Fluid Dynamics and Diffusion Laboratory, College of Engineering, Colorado State University, publisher (Colorado State University. Libraries, 1968)
Tests were conducted in the Colorado State University 2 m square by 80 m long speed wind tunnel to determine the distribution of gas concentrations resulting from gaseous plumes released from short stacks on top of a model of the Shoreham Nuclear Power Station reactor building. Basic tests were made on the reactor building model in an adiabatic atmosphere having a logarithmic upstream velocity profile. The effects of absolute wind velocity, and approach azimuth, and variable stack velocities were examined. Data obtained included photographs of model smoke plume trajectories, photographs of plume ground impingement shown by indicator points, and local concentrations of Kr-85 at downstream locations.
CER68-69RNM-JEC-FHC1.
Shoreham Nuclear Powerplant (N.Y.).
Under contract to Stone and Webster Engineering Corporation, Boston (Mass.).
July 1968.
Keywords: Wind tunnel models; Buildings -- Aerodynamics